NUP98‐BPTF gene fusion identified in primary refractory acute megakaryoblastic leukemia of infancy. Issue 6 (28th March 2018) - Roussy, Mathieu; Bilodeau, Mélanie; Jouan, Loubna; Tibout, Pauline; Laramée, Louise; Lemyre, Emmanuelle; Léveillé, France; Tihy, Frédérique; Cardin, Sophie; Sauvageau, Camille; Couture, Françoise; Louis, Isabelle; et al.
Abstract: The advent of large scale genomic sequencing technologies significantly improved the molecular classification of acute megakaryoblastic leukaemia (AMKL). AMKL represents a subset (∼10%) of high fatality pediatric acute myeloid leukemia (AML). Recurrent and mutually exclusive chimeric gene fusions associated with pediatric AMKL are found in 60%‐70% of cases and include RBM15‐MKL1, CBFA2T3‐GLIS2, NUP98‐KDM5A and MLL rearrangements. In addition, another 4% of AMKL harbor NUP98 rearrangements ( NUP98 r), with yet undetermined fusion partners. We report a novel NUP98‐BPTF fusion in an infant presenting with primary refractory AMKL. In this NUP98 r, the C‐terminal chromatin recognition modules of BPTF, a core subunit of the NURF (nucleosome remodeling factor) ATP‐dependent chromatin‐remodeling complex, are fused to the N‐terminal moiety of NUP98, creating an in frame NUP98‐BPTF fusion, with structural homology to NUP98‐KDM5A. The leukemic blasts expressed two NUP98‐BPTF splicing variants, containing one or two tandemly spaced PHD chromatin reader domains. Our study also identified an unreported wild type BPTF splicing variant encoding for 2 PHD domains, detected both in normal cord blood CD34 + cells and in leukemic blasts, as with the fly BPTF homolog, Nurf301. Disease course was marked by rapid progression and primary chemoresistance, with ultimately significant tumor burden reduction following treatment with a clofarabine containing regimen. In sum, we report 2 novel NUP98‐BPTF fusion isoforms that contribute to refine the NUP98 r subgroup of pediatric AMKL. Multicenter clinical trials are critically required to determine the frequency of this fusion in AMKL patients and explore innovative treatment strategies for a disease still plagued with poor outcomes.